2008
DOI: 10.1007/s10552-008-9139-4
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and prostate cancer risk in a large population-based setting

Abstract: Background-Statins are a commonly used cholesterol-lowering drug, which also have the potential to affect cancer risk and progression. Results from previous studies offer mixed conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 38 publications
0
63
0
2
Order By: Relevance
“…However, this association was not statistically significant nor was a dose dependent relationship observed. 20 Multiple theories for the role of statins in preventing metastatic or advanced prostate cancer have been proposed. In vitro the presence of statins has been known to cause apoptosis of prostate cancer cell lines directly.…”
Section: Discussionmentioning
confidence: 99%
“…However, this association was not statistically significant nor was a dose dependent relationship observed. 20 Multiple theories for the role of statins in preventing metastatic or advanced prostate cancer have been proposed. In vitro the presence of statins has been known to cause apoptosis of prostate cancer cell lines directly.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the results were controversial. Seven studies showed that statins were associated with a statistically significant cancer risk, with hazard ratios (HRs) or relative risks (RRs) > 1.0 [20][21][22][23][24][25][26]. Conversely, seven other studies reported statins were associated with a decreased cancer risk [21,[27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…12) Epidemiological studies have shown a reduced risk of advanced prostate cancer with the use of statins. [13][14][15][16] Statin use was also found to be associated with a reduction in the risk of biochemical recurrence in patients with prostate cancer 17) and a decreased risk of cancer mortality. 18) Recent studies have shown statin drugs including atorvastatin (Lipitor ® ) inhibit proliferation and induce apoptosis of prostate cancer cells.…”
mentioning
confidence: 99%